Sponsored Product-Based Competition and Customer Engagement: A Study of an Esports Competition in the Video Game Industry - Jo, Wooyong; Lewis, Michael (Production and Operations Management, 2024)
The sponsorship of sports or entertainment events is a long-established marketing promotion technique. The goals of sponsoring these events are to generate exposure and to transfer brand equity. A more assertive type of sponsored competition is when the competition is built around the products and brands of the sponsoring firm. The number of firms using sponsored product-based competitions (SPCs) is rising. Firms invest in these competitions to create content that highlights the capabilities of their products and build committed fan bases. However, evaluating the economic value of this type of sponsorship activity is challenging due to the absence of a direct link between event viewing and subsequent product consumption. We present an empirical approach to investigate the impacts of SPC on customer engagement using esports viewing and video game consumption data. We find that sponsored competitions provide firms with substantial benefits. Specifically, the results suggest that viewing an SPC event (i.e., esports competition) reduces consumers’ time between game plays by 3.2% (i.e., increased visit frequency), increases per-visit duration by 3.5%, and boosts the paid content purchase rate by 26%. These findings are corroborated using an alternate dataset from a second esports event from the game publisher. We find that the effect of an SPC event viewing is a nonlinear function of consumer expertise and is more pronounced among customers less familiar with the video game product category. In a supplementary analysis, we also identify an educational role of SPC that may explain the observed incremental consumption. The analyses reveal that esports audiences tend to choose frequently featured game characters with superior performance during the event. In addition, we find that when event viewers play the game with these characters, their performance improves. The results have substantial implications for event sponsorship management and follow-up product promotions.